1999
DOI: 10.1002/1529-0131(199907)42:7<1508::aid-anr26>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Production of interleukin-7 and interleukin-15 by fibroblast-like synoviocytes from patients with rheumatoid arthritis

Abstract: Objective. To examine the ability of fibroblast-like synoviocytes in rheumatoid arthritis (RA) to produce interleukin-7 (IL-7) and IL-15, and the ability of these cytokines to induce the proliferation of synoviuminfiltrating T cells.Methods. Messenger RNA (mRNA) and protein levels of IL-7 and IL-15 in synovial tissue cells and fibroblast cell lines were determined by reverse transcriptase-polymerase chain reaction and enzymelinked immunosorbent assay, respectively. T cellenriched populations from RA synovial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
116
2
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(122 citation statements)
references
References 46 publications
2
116
2
2
Order By: Relevance
“…IL-15 is known to stimulate activation, proliferation, survival, and effector functions of a variety of immune cells [15][16][17][18][19][20][21][22][23][24][25]. Increased expression of IL-15 in RA patients suggests that IL-15 is involved in the pathogenesis of RA [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-15 is known to stimulate activation, proliferation, survival, and effector functions of a variety of immune cells [15][16][17][18][19][20][21][22][23][24][25]. Increased expression of IL-15 in RA patients suggests that IL-15 is involved in the pathogenesis of RA [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of IL-15 was demonstrated not only in macrophages but also in endothelial cells and fibroblastlike synoviocytes, and the concentration of IL-15 in synovial fluids was shown to be elevated in RA patients [22][23][24][25][26]. It was also shown that IL-15 induced TNF-a production from macrophages through activation of synovial T cells in RA patients [27].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, FLS are important sources of IL-15 in RA joints. Indeed, IL-15 expressed by RA FLS may be responsible for intraarticular T cell activation and expansion (34). The aim of this study was to test the hypothesis that IL-15 is critical to FLS activation and survival.…”
mentioning
confidence: 99%
“…They produce chemotactic and proinflammatory cytokines that promote leukocyte infiltration in the joints (4)(5)(6)(7)(8)(9)(10). In addition, the FLS synthesize extracellular matrix proteins, such as fibronectin, that facilitate cell attachment to the articular surface and promote cell survival (1,2,11).…”
mentioning
confidence: 99%